Knowledge-based agent model of analysis management process of bankroll - Прохоров, Александр Валерьевич; Страшненко, Юлия Николаевна (Eastern-European Journal of Enterprise Technologies, 2012)
The article represents knowledge based agent imitation modeling of bankroll management processes. It provides the interrelation of many financial flows, requirements, objectives, behavior strategies of the separate bank departments. It describes dynamic of bankroll processes